Cyclopoid copepods in La Pampa Province (Argentina) (Semiárida, 2020)
The aim of this work are to extend the records of planktonic copepods of La Pampa province and lo give a brief diagnostic description of the main features of each species. I found 5 species quoted for the first time for the province: Acanthocyclops robustus, Mesocyciops meridianus, Metacyciops mendocinus, Microcylops anceps anceps and Tropocyciops prasinus meridionales.
Keywords: copepods; cyclopoids; La Pampa